In vitro ingestion and inhalation bioaccessibility of soilborne lead, cadmium, arsenic and chromium near a chemical industrial park for health risk assessment. Issue 1 (1st January 2019) - Hu, Xin; Zhang, Nan; Liu, Yuting
ABSTRACT: Surface soils were collected near a chemical industrial park in the present study and  in vitro  inhalation and ingestion bioaccessibility of soilborne lead, cadmium, arsenic and chromium was evaluated using various  in vitro  bioaccessibility procedures including simulated lung fluid (SLF), artificial lysosomal fluid (ALF), modified Gamble solution (MGS), Solubility/Bioaccessibility Research Consortium (SBRC) procedure, and  in vitro  gastrointestinal (IVG) procedure. The  in vitro  inhalation and ingestion bioaccessibility of toxic elements showed elemental dependence and differed greatly among SBRC, IVG, SLF, ALF and MGS. The non-carcinogenic and lifetime carcinogenic risks of soilborne toxic elements based on the bioaccessible contents via ingestion and inhalation exposure were within the acceptable level. The present study reveals that the  in vitro  bioaccessibility of toxic elements was influenced greatly by the current  in vitro  bioaccessibility procedures, which resulted in great differences on the risk-based assessment via inhalation and oral ingestion exposure.